Anemia and transfusion in the neonate. Issue 1 (February 2016) - Colombatti, Raffaella; Sainati, Laura; Trevisanuto, Daniele
Summary: Neonatal anemia is a frequent occurrence in neonatal intensive care units. Red blood cell transfusion criteria in case of blood loss are clearly defined but optimal hemoglobin or hematocrit thresholds of transfusion for anemia due to decreased production or increased destruction are less evident. This review focuses on the causes of anemia in the newborn period and the most recent evidence-based treatment options, including transfusion and erythropoiesis-stimulating agents.